EDUCATION LEVEL, SPECIAL AUTONOMY FUNDS, AND ECONOMIC GROWTH AS DETERMINANTS OF POVERTY IN REGENCIES/ MUNICIPALITIES OF ACEH PROVINCE - Ulfa Sunna; Ratna; Saharuddin Saharuddin; Mutia Rahmah (LPPM Universitas Malikussaleh, 2025)
This research investigates how education levels, Special Autonomy Funds, and economic growth influence poverty in the districts and cities of Aceh Province. The study uses panel data from 2019 to 2024, obtained from Statistics Indonesia (BPS) and the Directorate General of Fiscal Balance (DJPK), and applies panel regression analysis. Among the models tested, the Random Effects Model (REM) was identified as the most suitable approach. The results reveal that education expenditure and special autonomy funds significantly reduce poverty, whereas economic growth shows a positive but statistically insignificant effect. Combined analysis indicates that education levels, special autonomy funds, and economic growth together have a significant positive impact on poverty levels in Aceh’s districts and cities. Based on these findings, it is recommended that the Aceh government enhance investments in education and improve education quality through effective use of special autonomy funds. Such measures are expected to foster economic growth and contribute to the reduction of poverty across the province